Chronic Pain in the Outpatient Palliative Care Clinic. (March 2013) - Merlin, Jessica S.; Childers, Julie; Arnold, Robert M.
Chronic pain is common. Many patients with cancer and other life-limiting illnesses have chronic pain that is related to their disease, and some have comorbid chronic nonmalignant chronic pain. As palliative care continues to move upstream and outpatient palliative care programs develop, palliative care clinicians will be called upon to treat chronic pain. Chronic pain differs from acute pain in the setting of advanced disease and a short prognosis in terms of its etiology, comorbidities—especially psychiatric illness and substance abuse—and management. To successfully care for these patients, palliative care providers will need to learn new clinical competencies. This article will review chronic pain management core competencies for palliative care providers.